Credit constraints and exports: A survey of empirical studies using firm level data - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
Business managers are well aware of the fact that credit constraints can hamper or even prevent exporting. Economists only recently started to incorporate these arguments in theoretical models of heterogeneous firms and to test the implications of these models econometrically with firm-level data. Starting with the pioneering study by Greenaway, Guariglia and Kneller (Journal of International Economics, 2007) a growing number of empirical papers looked at the links between financial constraints and export activities using data at the level of the firm. This paper presents a tabular survey of 32 empirical studies that cover 14 different countries plus five multi-country studies. The big picture can be summarized as follows: Financial constraints are important for the export decisions of firms - exporting firms are less financially constrained than non-exporting firms. Studies that look at the direction of this link usually report that less constraint firms self-select into exporting, but that exporting does not improve financial health of firms. The paper argues that the results at hand should not be considered as stylized facts that can guide policy makers in an evidence-based way and suggests a strategy to further improve our knowledge in this area.
Keywords: F14; 330; Credit constraints; exports; empirical studies; literature survey